Aesthetics of everyday life: thematic variations and research prospects - Napadysta,; O. D. Rykhlitska, (Ukrainian Cultural Studies, 2022)
The article considers the peculiarities of the formation and thematic evolution of the aesthetics of everyday life. Emphasis is placed on the fact that the orientation of classical aesthetic theory on the artistic sphere left out of the attention of researchers non-artistic sources of aesthetic experience, and the versatility of the phenomenon of everyday life, its connotation with trivial, boring, routine, repetitive created certain prejudices for seeing the aesthetic component in everyday practices and recognizing the existence of objects of aesthetic experience among its material world.The scientific interest of aesthetic theory innovators, who expanded their creative search beyond the traditional research field, was initially focused mainly on design. Inclusion in the thematic palette of aesthetic research of design, natural environment opened the possibility of considering everyday practices as sources of aesthetic experience and caused a kind of "new turn" in aesthetic theory, which in turn led to the initiation and institutionalization of a new field of research – everyday aesthetics.In the context of its research is the variability of the material world, daily practices that ensure the functioning of a person as an individual in everyday life – gastronomic, physical, home improvement, organization of life, social contacts – regulatory stability, habitual strategies for communicating with others, and also routine daily activities – eating, walking, bathing, etc.It is emphasized that the variable saturation of the thematic field of everyday aesthetics, as a new direction in modern aesthetic theory, requires not only horizontal expansion of vectors of aesthetic research, but also theoretical clarification / justification / agreement on the content of the concepts of "everyday life" and "aesthetic" in the aesthetics of everyday life to delineate the boundaries of thematic definition and structure of its subject field.The application of the optics of cultural analysis regarding the origins and formation of aesthetics of everyday life as a separate direction, its thematic field and various interpretations of it will contribute not only to the systematization of knowledge about the path of formation and development of aesthetics of everyday life, but also to a deeper understanding of its potential as a productive theoretical basis in the process of aestheticizing everyday life.
Keywords: aesthetic theory; everyday life; everyday practices; aesthetics of everyday life; thematic field of the aesthetics of everyday life